Evaluation of in vitro anti-inflammatory and antibacterial potential of Crescentia cujete leaves and stem bark. (December 2015) - Parvin, Mst.; Das, Nandita; Jahan, Nusrat; Akhter, Most.; Nahar, Laizuman; Islam, Md.
Abstract Background The various parts ofCresecentia cujete have some important biological activities. In folklore medicine leaves are used to treat hematomas, tumors and hypertension. Fruit decoction is used to treat diarrhea, stomachaches, cold, bronchitis, cough, asthma, and urethritis. The present study was designed to explore the anti-inflammatory and antibacterial potential ofC. cujete leaves and stem bark. Anti-inflammatory activity was evaluated by in vitro human red blood cell (HRBC) membrane stabilization method and antibacterial activity by disc diffusion method. Methods In vitro anti-inflammatory activity was evaluated by human red blood cell (HRBC) membrane stabilization method while in vitro antibacterial activity was evaluated using cultures ofEscherichia coli andStaphylococcus aureus by disc diffusion method. Total phenolic (TPC) and total flavonoid contents (TFC) of the crude extract and fractions were also determined by Folin–Ciocalteu's phenol reagent and by aluminium chloride method, respectively. Results The crude ethanol extract (CEE) of leaves and bark (concentration of each 1.0 mg/ml) demonstrated strong membrane stabilizing activity (53.86 and 61.85 % protection, respectively), whereas their chloroform fractions (CHF) revealed moderate activity (48.74 ± 0.56 and 43.55 ± 6.20 %, respectively) compared with standard aspirin (concentration 0.10 mg/ml) which showed 75.81 % protection in this test. All the samples showed a dose dependent anti-inflammatory activity in HRBC membrane stabilization test. Total phenolic (TPC) and total flavonoid contents (TFC) of the crude extract and fractions were also determined. Again, in in vitro antibacterial study, the extractives exhibited potent antibacterial activity. Conclusion Results from this study showed that the leaves and bark ofC. cujete possessed anti-inflammatory as well as antibacterial activities indicating that the plant extract has therapeutic potential against the bacterial infection and also have effect on disease processes by causing destabilization of biological membranes.